A Multilab Study of Bilingual Infants: Exploring the Preference for Infant-Directed Speech. Issue 1 (March 2021) - Byers-Heinlein, Krista; Tsui, Angeline Sin Mei; Bergmann, Christina; Black, Alexis K.; Brown, Anna; Carbajal, Maria Julia; Durrant, Samantha; Fennell, Christopher T.; Fiévet, Anne-Caroline; Frank, Michael C.; Gampe, Anja; Gervain, Judit; et al.
From the earliest months of life, infants prefer listening to and learn better from infant-directed speech (IDS) compared with adult-directed speech (ADS). Yet IDS differs within communities, across languages, and across cultures, both in form and in prevalence. This large-scale, multisite study used the diversity of bilingual infant experiences to explore the impact of different types of linguistic experience on infants' IDS preference. As part of the multilab ManyBabies 1 project, we compared preference for North American English (NAE) IDS in lab-matched samples of 333 bilingual and 384 monolingual infants tested in 17 labs in seven countries. The tested infants were in two age groups: 6 to 9 months and 12 to 15 months. We found that bilingual and monolingual infants both preferred IDS to ADS, and the two groups did not differ in terms of the overall magnitude of this preference. However, among bilingual infants who were acquiring NAE as a native language, greater exposure to NAE was associated with a stronger IDS preference. These findings extend the previous finding from ManyBabies 1 that monolinguals learning NAE as a native language showed a stronger IDS preference than infants unexposed to NAE. Together, our findings indicate that IDS preference likely makes similar contributions to monolingual and bilingual development, and that infants are exquisitely sensitive to the nature and frequency of different types of language input in their early environments.